Flamenco Guitar Sound : Documenting the Heritage - Robert Mores (Deutsche Gesellschaft für Akustik e.V. (DEGA), 2019)
The Flamenco guitar has its roots in the accompaniment of singing anddancing, with a dominant focus on fast and percussive sound. Since thedays of Paco de Lucia, the Flamenco guitar has also developed soundfeatures for solo performance, such as sustain, or fullness. The docu-mentation project seeks to capture the acoustics of Flamenco guitarsover the last 50 years, deriving robust features for classifications andtrend analyses. Along diverse temporal and spectral features the Flamenco guitar is benchmarked against the classical Spanish guitar, andits acoustical development is documented.